(926) A Model for the Optimal Use of the High Dam Project نموذج للاستخدام الأمثل لمشروع السد العالي - Mohammed Yehia Youssef. (معهد التخطيط القومى, 2024)
The High Dam project aims to utilize Nile River water in various ways to achieve multiple benefits such as irrigation development, agricultural land expansion, electricity generation, flood protection, inland water navigation improvement, shore cultivation, and fishery. Selecting the best method for operating the High Dam and developing new resources is crucial for accelerating economic growth and social progress.